Formal description technique to support load modelling for innovative communication systems - Magott, Jan; Wolfinger, Bernd (Zielona Góra: Uniwersytet Zielonogórski)
In order to evaluate the performance of computer and communication systems under realistic boundary conditions, adequate load models are urgently required. It is desirable to derive those models directly from load measurements. In this paper, Petri net based' models for users of innovative communication systems are presented. First, a survey of basic requirements to a formal load description technique is given.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka